Young's Modulus prediction of polyurethane and acrylonitrile butadiene styrene polymer blend based on phase morphology - Farzaneh Memarian; Abdolhossein Fereidoon; Morteza Ghorbanzadeh Ahangari (مجله مدل سازی در مهندسی, 2018)
Young's modulus of blends of thermoplastic polyurethane (TPU) and acrylonitrile butadiene styrene (ABS) are measured with different weight percentage (blend ratio). The results of the different micromechanical models prediction of Young's modulus, based on both droplet matrix and co-continuous morphology, are compared with experimental results. Both two-dimentisional models like series, parallel, Maxwell, Halpin-Tsai, Takayanagi, Davis, Coran and Patel, and three-dimensional models like Kolarik, Barentson and Nijhof are used for Young's modulus prediction of polymer blends. In this work, an emphasis was given to the effect of weight percentage on morphology and mechanical properties of the blend. Scanning electronic microscopy shows droplet matrix morphology in the presence of less than 20 wg% ABS in TPU matrix but in 70/30 TPU/ABS blend ratio, ABS phase dispersed like elongated elliptical and phase inversion happened. In the 95/5, 90/10 and 80/20 blend ratio  which ABS droplets dispersed uniformly throughout the TPU matrix, Parallel Takayanagi and Barentson series model of parallel parts, could predict Young's modulus with good accuracy. In the 70/30 blend ratio which phase inversion was observed and both phases are somehow continuous, Coran-Patel, series Nijhof and Kolarik models were accurate.